Socio-Demographic and Parental Acceptability of Covid-19 Pediatric Vaccination of Children with Co-Morbidities - Orte, Christian Jay S.; Ganzon, Sheree G.; Morales, Ma. Theresa D.; Santos-Matibag, Ruby (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The COVID-19 pandemic has significantly impacted public health worldwide, with children being a particularly vulnerable population due to their developing immune systems. Children with co-morbidities, such as asthma, diabetes, and other chronic conditions, are at a higher risk of severe outcomes from COVID-19 infection. The study aims to determine if the sociodemographic profile attributes may tend to have a relationship in accepting COVID-19 vaccination for parents with children with co-morbidities. Descriptive-correlational design was used in this study involving 46 participants either the mother or father of the child, Filipino residents near the declared research locale and have children who were 5 to 11 years of age situated in one municipality in Bataan, Philippines recruited us-ing a purposive sampling technique. A self-made non-standardized instrument was used in this study (a=0.78). The gathered data was analyzed using descriptive mean and Spearman Rho. Results indicate that COVID-19 pediatric vaccination is highly acceptable among the respondents (M=3.42, SD=0.34). As such, sex as demographic profile (rs=.486, p=0.001) revealed significant findings regarding parent’s acceptability of COVID-19 pediatric vaccination. The findings of this study indicated that sex-specific factors may influence vaccine ac-ceptability, and public health strategies should consider tailoring in-terventions to address these factors to promote COVID-19 vaccina-tion acceptance.